2021
DOI: 10.1017/jfm.2021.273
|View full text |Cite
|
Sign up to set email alerts
|

Two-layer fluid flows on inclined surfaces

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…By contrast, when the lower layer is more mobile (e.g. figure 4 b ), the flux in the upper layer varies non-monotonically with hu=1hl due to the strong effect of lubrication; at low values of hl, small increases in hl actually increase the upper layer flux even though the upper layer is thinner (for an in-depth investigation of two-layer Newtonian flow on an inclined plane, see Shah et al [10]). Similar features can be observed in figure 4 d .…”
Section: Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, when the lower layer is more mobile (e.g. figure 4 b ), the flux in the upper layer varies non-monotonically with hu=1hl due to the strong effect of lubrication; at low values of hl, small increases in hl actually increase the upper layer flux even though the upper layer is thinner (for an in-depth investigation of two-layer Newtonian flow on an inclined plane, see Shah et al [10]). Similar features can be observed in figure 4 d .…”
Section: Case Studiesmentioning
confidence: 99%
“…Both these two-layer studies found that in the limit of equal density fluids, a frontal shock forms and this is associated with the hydrostatic pressure gradients that drive the flow becoming independent of the shape of the interface between the fluids. Flow on an inclined plane has also been investigated for one layer [9] and two layers [10] of Newtonian fluid with various steady flows and similarity solutions obtained. Two-layer flows in porous media lead to simpler governing equations than the viscous case but there is still a multiplicity of possible flow regimes that can occur depending on the viscosity, volume and density ratios [11].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, they can merge instead of passing through each other without significant change, with the latter being the case of two solitary waves governed by the well-known KdV equation [3,32]. The analysis of solitary-like surface waves in flowing liquid films is also important because liquid films, as well as similar physical systems [33][34][35], are often encountered in the fields of earth and planetary sciences [36,37] and in technological processes [38], where the liquids of interest can also experience temperature gradients [14,28] and vibrations [39][40][41]. Given this, the effect of vibrations on the wave dynamics of film flows has become an independent subject of fundamental and applied research [42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%